Bhinneka Tunggal Ika [Unity in Diversity]: From Dynastic Policy to Classroom Practice - Mohammad Imam Farisi (Journal of Social Science Education, 2014)
The purpose of this article is to discuss the concept of Bhinneka Tunggal Ika, in its narrowest sense, a policy on religious tolerance, as it is operationalized in social studies textbooks and in classroom practice in Indonesia. The focus of the research is on six electronic textbooks used by students aged 7-12 years, in Indonesian elementary schools which are further considered in the context of Indonesian teachers’ actual experience of the operationalisationof Bhinneka Tunggal Ika in a classroom setting. The study shows that the textbooks and classroom practice are able to describe and transform a concept such as  Bhinneka Tunggal Ika into a real and meaningful concept or practice for students as practiced in the family, the school, the wider community and at a national level as well as in  religious ceremonies, architecture, and gotong-royong (or reciprocal) activities. However, the state also has a political goal and this concept should also be viewed as underlying cultural policy designed to build a character and civilization appropriate to a pluralistic Indonesian nation.